Student perspectives of a Student‐Led Groups Program model of professional practice education in a brain injury rehabilitation unit. (7th April 2017) - Patterson, Freyr; Fleming, Jennifer; Marshall, Kathryn; Ninness, Nadine
Abstract : Background/aim: Professional practice education is a core and essential component of occupational therapy training. With increasing numbers of education programmes and more students requiring professional practice placements, development of innovative models of professional practice education has emerged, but these require investigation. The aim of this study was to investigate student experiences and perceptions of the Student‐Led Groups Program model of professional practice education in an inpatient brain injury rehabilitation unit. Methods: A qualitative approach, guided by phenomenological theory was used. Participants were 15 students who had completed a professional practice placement in the Student‐Led Groups Program. Data were collected using in‐depth semi‐structured interviews and analysed thematically. Results: Three over‐arching themes emerged from the data; balance of support and freedom, development of clinical skills and missed opportunities. Students described how the structure of the placement facilitated independent learning and autonomy that was balanced with support from clinicians and student peers. Students perceived that they had developed a breadth of clinical skills and also had missed some learning opportunities in this professional practice placement structure. Conclusions: Overall student perceptions of the Student‐Led Groups Program were positive, supporting the continued use of this model of professional practice education in this setting. The results highlight the value of structured and consistent approaches for supervision, including the use of formal approaches to peer supervision in the initial stages of learning.